Increased risk of adverse drug events secondary to bevacizumab treatment in patients with advanced or metastatic breast cancer: A meta-analysis of randomized controlled trials - Shin, Sooyoung; Noh, Yoojin (Therapeutics and Clinical Risk Management, 2018)
Background: Several clinical trials have shown an increased risk of hypertension with bevacizumab when added to chemotherapy in different types of malignancy; however, the risks of other significant adverse events besides hypertension, specifically in breast cancer, have not been completely elucidated. This study was conducted with the aim, primarily, to assess the overall incidence and risk of common toxicities associated with bevacizumab in patients with advanced or metastatic breast cancer and, secondarily, to descriptively review study results concerning a potential correlation between bevacizumab-induced hypertension and its efficacy for breast cancer treatment. Methods: We carried out a meta-analysis of relevant randomized controlled trials (RCTs) identified from a database search (Cochrane Library and PubMed) and, additionally, by reviewing previous reviews and meta-analyses. Overall incidence rates, odds ratios (ORs), and 95% confidence intervals (CIs) were assessed with the random- or fixed-effect models, depending on the level of heterogeneity across the included trials. The primary clinical outcomes were high-grade adverse events commonly reported with bevacizumab therapy. Results: We included 6,260 patients with advanced-stage breast cancer from 12 RCTs in the meta-analysis. Five types of high-grade (Grade 3 or 4) adverse drug events were identified as being correlated with bevacizumab treatment versus alternative treatment with statistical significance: hypertension (OR 5.67, 95% CI 3.02–10.65), proteinuria (OR 10.09, 95% CI 4.79–21.27), bleeding (OR 3.45, 95% CI 2.25–5.30), cardiac toxicity (OR 2.15, 95% CI 1.29–3.59), and neutropenic fever (OR 1.51, 95% CI 1.15–2.00). The prognostic value of bevacizumab-induced hypertension for its antitumor efficacy among patients with breast cancer remains controversial, with mixed results presented in the five retrospective studies that were identified from our additional literature search. Conclusion: The addition of bevacizumab to anticancer therapy was associated with a significant increase in the risk of high-grade adverse events, including hypertension, proteinuria, bleeding, cardiac toxicity, and neutropenic fever among patients with advanced-stage breast cancer. Although several retrospective studies suggested a predictive importance of hypertension secondary to bevacizumab therapy, the role of elevated blood pressure as a prognostic biomarker for its antitumor efficacy remains controversial, and further prospective trials are required to confirm such a correlation.
Keywords: Adverse events; Bevacizumab; Biomarker; Breast cancer; Hypertension; Metastatic disease